PENGALAMAN EKSPLORASI PERTUNJUKAN TARI DALAM ACARA PEMBUKAAN FESTIVAL SEBAGAI TEMUAN METODE CIPTA SENI (Studi Kasus Proses Penciptaan Karya Tari Seno Kridho) - Samsuri, S.,; Wibowo, Anggono Kusumo (Acintya, 2017)
In the domain of public dance performances, aspects of space, time, and particular interests greatlyaffected creative outcomes. Space, time, and particular interests were sometimes considered as limiting the creativity. In this art work planning, the limitation of space, time and interests were used as atrigger for creativity. On this occasion the dance performance creation would be directed to make aset of dance performances as a festival opening by carrying a wayang story titled â€œDewa Ruciâ€, andtrying to show typical performance requirements for a festival opening ceremony, namely: festive, fullof surprises, message events, and still pay consideration to the dramaturgy impression in the packaging. Dance performances as the opening of a festival was a form of performances packaging thatwere within the limits of space, time, and particular interests, it could not be negotiated. While theshort duration still demanded excitement and surprise, the message content of the event must beshown in the work. This became a huge creative challenge for an artist. The experience of creating aperformance in this interest context, became a methodological experience that could be proposed asa finding.Keywords: festival opening perfomance packaging, drama â€œDewa Ruciâ€.